2016
DOI: 10.1371/journal.pone.0149897
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammation Promotes Expression of Stemness-Related Properties in HBV-Related Hepatocellular Carcinoma

Abstract: The expression of cancer stemness is believed to reduce the efficacy of current therapies against hepatocellular carcinoma (HCC). Understanding of the stemness-regulating signaling pathways incurred by a specific etiology can facilitate the development of novel targets for individualized therapy against HCC. Niche environments, such as virus-induced inflammation, may play a crucial role. However, the mechanisms linking inflammation and stemness expression in HCC remain unclear. Here we demonstrated the distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…An aspect here that remains elusive to the scope of the present study is how the loss of RhoA (which alters the mechanical and biochemical properties of normal stromal fibroblasts) can trigger a stem-like phenotype in these PC3 prostate cancer cells. Probably, increased level of proinflammatory genes plays role in inducing the expression of stemness-related properties of tumor cells (38,39). We have demonstrated that loss of RhoA changed the cytoskeleton, the contractile forces and cell stiffness of the cells, induced a proinflammatory state, and interfered with Rho signaling cascades.…”
Section: Discussionmentioning
confidence: 88%
“…An aspect here that remains elusive to the scope of the present study is how the loss of RhoA (which alters the mechanical and biochemical properties of normal stromal fibroblasts) can trigger a stem-like phenotype in these PC3 prostate cancer cells. Probably, increased level of proinflammatory genes plays role in inducing the expression of stemness-related properties of tumor cells (38,39). We have demonstrated that loss of RhoA changed the cytoskeleton, the contractile forces and cell stiffness of the cells, induced a proinflammatory state, and interfered with Rho signaling cascades.…”
Section: Discussionmentioning
confidence: 88%
“…However, several studies have indicated that tumor pathogenesis and progression are closely associated with the tumor microenvironment, as well as tumor cells themselves (13). Recent studies have suggested that a systemic inflammatory state is associated with the malignant biological behavior of the tumor (14,15). In particular, the neutrophil-lymphocyte ratio (NLR) has been evaluated as a predictor of prognosis in various types of solid tumor, including gastric, colorectal, pancreatic, breast and lung cancers (16)(17)(18)(19)).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of stemness-related genes in cancer is likely linked to the generation and evolution of the compartment of cells able to regenerate tumor diversity, the cancer stem cells (CSCs) (Kuo et al, 2016; Uthaya Kumar et al, 2016). Upregulation of OCT4 has been shown to contribute to tumor cell migration and resistance to cancer therapeutics (Ma et al, 2011; Chang et al, 2015, 2016; Bhatt et al, 2016). …”
Section: Inflammatory Signaling During Diseasementioning
confidence: 99%